2005
DOI: 10.1021/ac048535o
|View full text |Cite
|
Sign up to set email alerts
|

Cytometry and Velocimetry on a Microfluidic Chip Using Polyelectrolytic Salt Bridges

Abstract: This paper reports a polyelectrolytic salt bridge-based electrode (PSBE), which is a key embedded unit in a microchip device that can size-selectively count microparticles and measure their velocities. The construction of salt bridges at specific locations within a microfluidic chip enables dc-driven electrical detection to be performed successfully. This is expected to be a competitive alternative to the optical methods currently used in conventional cell sorters. The PSBEs were fabricated by irradiating ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 36 publications
1
71
0
1
Order By: Relevance
“…We demonstrated that a decrease in the distance between the sensor and the particle can increase the particle size resolution, but limits the range of detection. The simultaneous and automated detection of velocity and size of single particles enables a wide range of particle characterizations and offers many applications in bio-analytical systems [20]. Since the principles of actuation and detection are not coupled, we can envisage using the particles as mobile substrates to transport biomaterials of interest, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that a decrease in the distance between the sensor and the particle can increase the particle size resolution, but limits the range of detection. The simultaneous and automated detection of velocity and size of single particles enables a wide range of particle characterizations and offers many applications in bio-analytical systems [20]. Since the principles of actuation and detection are not coupled, we can envisage using the particles as mobile substrates to transport biomaterials of interest, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…100,101 Although other metal electrodes can be more readily integrated into microfluidic channels, the electrical double layers formed between the interface of electrodes and the liquid, which are mainly capacitive, pose difficulties in applying DC signals. Methods for minimizing the electrical double layer effect include the modification of the electrode surface roughness in order to increase the surface area 102 and the utilization of polyelectrolytic salt bridges (PSBEs) 103 or polyelectrolyte gel electrodes (PGEs). 104 Most recently, a DC impedance-based microcytometer device integrating PGEs was reported for CTC cell detection.…”
Section: Microfluidic Coulter Countermentioning
confidence: 99%
“…Low-frequency or DC input can also cause Faradaic reactions at metal electrodes, causing them to erode. Chun et al have developed salt-bridge based electrodes (72) to improve the sensitivity of particle sizing. The salt bridges fabricated by Chun et al consisted of microfluidic channels filled with NaCl solution, into which Ag/AgCl electrodes were immersed.…”
Section: Microfluidic Coulter Systems Sensitivitymentioning
confidence: 99%